Socio-Cultural Relationship of The Tondano Javanese Community with The Original Minahasa Community - Muhammad Fajar Hidayat; Veronike E.T Salem; Paulus R. Tuerah; Romi Mesra (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The history of local interaction between the Minahasa people and the Javanese Tondano because of the many similarities between many aspects of the life of these people, especially peaceful family ties, it is predicted that there will be no ripples of conflict in the future in Kampung Jawa Tondano which is too significant. This research will describe how the Javanese Tondano people and the Minahasa people interact in the Jawa Tondano Village. This study uses a qualitative research approach. According to the findings of this study, the relationship between the Tondano Javanese Muslim community and the Minahsa Christian community has never experienced conflict since the first time the Javanese arrived in Minahasa, all communities are very harmonious and respect each other among religions and also through marriage, kinship, and also their currency. as a social forum to meet two different cultures. The findings of this research are expected to be of use to academics, particularly in the fields of sociology and culture, as well as the general public.